Penggunaan Bahasa Indonesia Pada Iklan Ditelevisi Dan Radio - Ariel Adriansyah (Student Scientific Creativity Journal, 2023)
The research entitled Use of Language in advertisements and broadcasts on TV. The formulation of the problem is (1) How is the use of the variety of spoken language? (2) How is the use of languageseen from the accuracy of the choice of words (diction)? (3) How is the code mixing that occurs in the use of the language, the method used is a qualitative descriptive method. The source of the data used in this research is the oral utterances delivered in broadcast news. Source of data used as research data is news that is broadcast starting from the morning and at night. Technique data collection in this study used the recording method with listening and listening techniques note technique. The results of the research show that (1) the use of speech variety is variety official (2) the use of diction, then 10 of the ten news used is obtained. Of the ten types of accuracy of diction analyzed, the results of the accuracy of the use of diction were obtained, as follows: use of special general words 6, use of words that are almost synonymous 5, use of denotative and connotative words 4, use of words that are similar in spelling 1, use of idioms 1, use of foreign endings 1, and use of continuity word choice 4 found inaccurate word choice. (3) the use of mixing Indonesian code into the language Region is code mixing into (inner code-mixing) due to code mixing carried out between local languages ​​and Indonesian. based on the results obtained the researcher's observation in depth, from the use of the language used is sufficient light what else is the local language and most of the errors found are correct used. Then mix the code that is widely used in broadcast news and advertisements should be avoided because it is news for the area and speak the local language.